"How long will I continue to be normal?" Adults with a Fontan circulation's greatest concerns. (1st June 2018) - du Plessis, Karin; Peters, Rebecca; King, Ingrid; Robertson, Kirsty; Mackley, Jonathan; Maree, Rachel; Stanley, Tracy; Pickford, Louise; Rose, Brian; Orchard, Matthew; Stewart, Helen; d'Udekem, Yves
Abstract: Background: Little is known about adults living with a Fontan circulation's concerns outside the scope of their clinical outcomes. We examined adults with a Fontan circulations' greatest concerns, as well as their concerns around anti-coagulation, pregnancy and finances. Methods: Adults with a Fontan circulation in the Australian and New Zealand Fontan Registry were invited to complete an anonymous online survey, of which 57 participated. A qualitative method approach using thematic analyses was used. Results: The greatest concerns for adults living with a Fontan circulation were fear of death/uncertainty around life expectancy which for many individuals colored their concerns around physical health, pregnancy and having children, quality of life and finances. Improving information about outcomes to patients with a Fontan circulation might alleviate uncertainties about their future. Conclusions: Fear of death is the primary concern of adults with a Fontan circulation. It may require improved communication and targeted psychological interventions. Physical exercise incorporated as part of their lifestyle should be encouraged to alleviate physical concerns and also improve psychological well-being. Highlights: Fontan adults' greatest concerns are fear of death and life expectancy uncertainty. Clear communication around outcomes could help alleviate these uncertainties. Targeted psychological support around fear of death could be beneficial. Lifestyle-integrated physical exercise could alleviate physical concerns.